2020
DOI: 10.1055/a-1261-3151
|View full text |Cite
|
Sign up to set email alerts
|

The National Endoscopy Database (NED) Automated Performance Reports to Improve Quality Outcomes Trial (APRIQOT) randomized controlled trial design

Abstract: Background and study aims Colonoscopists with low polyp detection have higher post colonoscopy colorectal cancer incidence and mortality rates. The United Kingdom’s National Endoscopy Database (NED) automatically captures patient level data in real time and provides endoscopy key performance indicators (KPI) at a national, endoscopy center, and individual level. Using an electronic behavior change intervention, the primary objective of this study is to assess if automated feedback of endoscopist and endoscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…A colonoscopy BCI with task-motivation plans and supplemental educational material are being tested in the NED APRIQOT study. [20] An A&F intervention aimed at improving leadership training in centre leads demonstrated improved colonoscopy performance centre wide [49]. Our study demonstrated that where there is underperformance in behaviours related to meta-tasks, such as poor completion rates due to endoscopist con dence, then addressing this is a complex social task.…”
Section: Measuring Performancementioning
confidence: 67%
See 3 more Smart Citations
“…A colonoscopy BCI with task-motivation plans and supplemental educational material are being tested in the NED APRIQOT study. [20] An A&F intervention aimed at improving leadership training in centre leads demonstrated improved colonoscopy performance centre wide [49]. Our study demonstrated that where there is underperformance in behaviours related to meta-tasks, such as poor completion rates due to endoscopist con dence, then addressing this is a complex social task.…”
Section: Measuring Performancementioning
confidence: 67%
“…Six English NHS endoscopy centres eligible for the NED-APRIQOT study were contacted by email, selected with convenience sampling for participants' availability. Eligible endoscopists [20] were purposively sampled with criteria comprising length of endoscopy experience and professional role (clinical lead, clinical-nurse endoscopist, gastroenterologist, surgeon, and trainee). Recruitment continued until sampling strata were lled and data saturation was reached, de ned as no new themes arising in the last three interviews after 10 complete interviews.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[32][33][34][35][36][37][38] The impact of automated feedback of NED KPIs on endoscopists and endoscopy leads is the current study area in a multicentre randomised controlled trial. 39 The differences in PDR between surgeons and gastroenterologists have been conflicting. 5 40 41 In a recent study of non-screening colonoscopies, 9 we found significant CWT and PDR variations among different groups of endoscopists according to their specialties.…”
Section: Discussionmentioning
confidence: 99%